Vitamin E and memantine in Alzheimer's disease: Clinical trial methods and baseline data. Issue 1 (15th April 2013) - Dysken, Maurice W.; Guarino, Peter D.; Vertrees, Julia E.; Asthana, Sanjay; Sano, Mary; Llorente, Maria; Pallaki, Muralidhar; Love, Susan; Schellenberg, Gerard D.; McCarten, J. Riley; Malphurs, Julie; Prieto, Susana; et al.
Abstract: Background: Alzheimer's disease (AD) has been associated with both oxidative stress and excessive glutamate activity. A clinical trial was designed to compare the effectiveness of ( i ) alpha‐tocopherol, a vitamin E antioxidant; ( ii ) memantine (Namenda), an N‐methyl‐D‐aspartate antagonist; ( iii ) their combination; and ( iv ) placebo in delaying clinical progression in AD. Methods: The Veterans Affairs Cooperative Studies Program initiated a multicenter, randomized, double‐blind, placebo‐controlled trial in August 2007, with enrollment through March 2012 and follow‐up continuing through September 2012. Participants with mild‐to‐moderate AD who were taking an acetylcholinesterase inhibitor were assigned randomly to 2000 IU/day of alpha‐tocopherol, 20 mg/day memantine, 2000 IU/day alpha‐tocopherol plus 20 mg/day memantine, or placebo. The primary outcome for the study is the Alzheimer's Disease Cooperative Study/Activities of Daily Living Inventory. Secondary outcome measures include the Mini‐Mental State Examination; the Alzheimer's Disease Assessment Scale, cognitive portion; the Dependence Scale; the Neuropsychiatric Inventory; and the Caregiver Activity Survey. Patient follow‐up ranged from 6 months to 4 years. Results: A total of 613 participants were randomized. The majority of the patients were male (97%) and white (86%), with a mean age of 79 years. The mean Alzheimer's Disease Cooperative Study/Activities of Daily Living Inventory score at entry was 57 and the mean Mini‐Mental State Examination score at entry was 21. Conclusion: This large multicenter trial will address the unanswered question of the long‐term safety and effectiveness of alpha‐tocopherol, memantine, and their combination in patients with mild‐to‐moderate AD taking an acetylcholinesterase inhibitor. The results are expected in early 2013.